Chemo-, regio- and stereo-selective aerial oxidation of limonene to the endo-1,2-epoxide over Mn(Salen)-sulfonated SBA-15 - Saikia, Lakshi; Srinivas, D.; Ratnasamy, Paul (Applied Catalysis A-General, 2006)
Mn(Salen) complexes immobilized on sulfonic acid-functionalized SBA-15 molecular sieves (SBA-15-pr-SO3-Mn(Salen)) catalyze the Mukaiyama-type oxidation of R-(+)-limonene selectively to the 1,2-epoxide with molecular oxygen at 298 K (Salen = N,N-ethylenebis(salicylidenaminato)). The endo-diastereomer is formed with a diasteromeric excess of 39.8%. This catalyst exhibited higher catalytic activity than ``neat'' Mn(Salen) complexes directly supported on SBA-15 or zeolite-Y. A change in the oxidation state of Mn from +3 in the ``neat'' complex to +2 when immobilized on the sulfonated surface is a probable cause for the observed enhancement of catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aerial oxidation of limonene; catalysis by Mn(Salen) complexes; chemo-; immobilized Mn Schiff base complexes; Mesoporous molecular sieves; Mukaiyama-type oxidation; regio- and stereo-selective epoxidation; sulfonic acid-functionalized SBA-15

Comparative catalytic activity of Mn(Salen) complexes grafted on SBA-15 functionalized with amine, thiol and sulfonic acid groups for selective aerial oxidation of limonene - Salkia, Lakshi; Srinivas, Darbha; Ratnasamy, Paul (Microporous and Mesoporous Materials, 2007)
SBA-15 molecular sieves were functionalized with propylamine, propylthiol and propylsulfonic acid groups. Mn(Salen)Cl complexes were grafted on these organo-functionalized SBA-15. The support and the type of organo-functional group influenced the electronic structure (oxidation state and redox behavior) and chemo selectivity of the Mn-complexes in the oxidation of limonene. The Mn ions were reduced from +3 to +2, the extent of this reduction on different supports decreasing in the order: SBA- 15-pr-SH > SBA- 15-prSO(3)H > SBA-15-pr-NH2- Mn(Salen)Cl supported on propylthiol-functionalized SBA-15 yielded the 1,2-limonene epoxide with 100% chemo- and regioselectivity. Higher electron density at the site of Mn ions and the consequent lower redox potential of the Mn-complexes on immobilization are the probable causes for their efficient and selective catalytic activity. Solvents, additives (N-MeIm) and co-reagents (iso-butyraldehyde), which facilitated formation of Mn2+ ions, enhance the catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction and the extent of this with different catalysts decreased in the order: SBA-l5-pr-NH2-Mn(Salen)Cl > SBA- 15-pr-SO3H-Mn(Salen)Cl > SBA- 15-pr-SH-Mn(Salen)Cl. (C) 2007 Elsevier Inc. All rights reserved

Catalytic activity of ZIF-8 in the synthesis of styrene carbonate from CO2 and styrene oxide - Zhu, Minqi; Srinivas, Darbha; Bhogeswararao, Seemala; Ratnasamy, Paul; Carreon, Moises A. (Catalysis Communications, 2013)
The catalytic activity of ZIF-8 in the synthesis of styrene carbonate from carbon dioxide and styrene oxide is presented. ZIF-8 crystals displayed catalytic activity even at temperatures as low as 50 degrees C, with styrene carbonate yields as high as similar to 54% at 100 degrees C. In contrast to many prior-art catalysts, solvents or co-catalysts were not required. Pyridine and ammonia were used as probe molecules to estimate the type and density of acid sites in fresh and reused ZIF-8 catalysts. DRIFT spectroscopy of adsorbed pyridine revealed the presence of both Bronsted (B) and Lewis (L) acid sites. The B-sites have nearly vanished in the case of recycled ZIF-8 catalysts. The simultaneous presence of both the acid sites and the nitrogen basic moieties from the imidazole linker in ZIF-8 promoted the adsorption of the CO2 on the solid surface and its further conversion to the cyclic carbonate. The ZIF-8 catalysts could be recycled and reused without significant loss in catalytic activity. Published by Elsevier B.V.
Keywords: CO2 conversion; cyclic carbonates; Styrene carbonate; Zeolitic imidazolate frameworks; ZIF-8